PENDEKATAN CRT : INOVASI PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF SISWA KELAS 3 SEKOLAH DASAR MATERI PECAHAN - Nuzul Nurhidayah; Dera Suci Aprilia Sari; Hendra Erik Rudyanto (CV. Adiba Aisha Amira, 2025)
The mathematics learning outcomes of third-grade students at SD Negeri Banjarsari Wetan 01 on fraction material were relatively low. This study aims to enhance students' cognitive abilities through the implementation of the Culturally Responsive Teaching (CRT) approach. The research employed a Classroom Action Research (CAR) method consisting of two cycles, with each cycle comprising one meeting. The study was conducted at SD Negeri Banjarsari Wetan 01 Dagangan, Madiun, involving 9 third-grade students as research subjects. In the pre-cycle stage, only 35% of students achieved the minimum learning mastery. This figure significantly increased to 50% in the first cycle and 85% in the second cycle. These findings indicate that the CRT approach is effective in improving students' cognitive abilities in mathematics, particularly in fraction material.